2017
DOI: 10.1186/s13287-017-0606-2
|View full text |Cite
|
Sign up to set email alerts
|

Cell sex affects extracellular matrix protein expression and proliferation of smooth muscle progenitor cells derived from human pluripotent stem cells

Abstract: BackgroundSmooth muscle progenitor cells (pSMCs) differentiated from human pluripotent stem cells (hPSCs) hold great promise for treating diseases or degenerative conditions involving smooth muscle pathologies. However, the therapeutic potential of pSMCs derived from men and women may be very different. Cell sex can exert a profound impact on the differentiation process of stem cells into somatic cells. In spite of advances in translation of stem cell technologies, the role of cell sex and the effect of sex ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 60 publications
1
11
0
Order By: Relevance
“…Sex hormones and receptors have also been shown to affect only female hematopoietic stem cell self-renewal 36 . Distinctions in proliferation of smooth muscle progenitor cells derived from hPSCs have also been shown as a function of cell sex in addition to disparity in extracellular matrix protein expression in these cells; however, no difference in differentiation efficiency was observed 37 . Differences in autosomal gene expression between male and female hPSCs have been reported, suggesting that male and female cells could respond differently to the same differentiation stimuli 38 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sex hormones and receptors have also been shown to affect only female hematopoietic stem cell self-renewal 36 . Distinctions in proliferation of smooth muscle progenitor cells derived from hPSCs have also been shown as a function of cell sex in addition to disparity in extracellular matrix protein expression in these cells; however, no difference in differentiation efficiency was observed 37 . Differences in autosomal gene expression between male and female hPSCs have been reported, suggesting that male and female cells could respond differently to the same differentiation stimuli 38 .…”
Section: Introductionmentioning
confidence: 99%
“…Many methods, currently used to generate endothelial progenitors for further differentiation to hemogenic or endothelial lineages, rely on the use of VEGF among other growth factors 10,37,39,40 . Based on previous experiments, the addition of Sunitinib, a VEGF receptor inhibitor, at any stage of the endothelial progenitor differentiation will result in abrogation of the endothelial progenitor population, which highlights the importance of endogenous VEGF pathway in endothelial progenitor differentiation 27 .…”
Section: Introductionmentioning
confidence: 99%
“…Ample evidence supports the notion that there are donor-dependent associations between directional differentiation capacity and vascular support of MSCs. Moreover, studies focused on the sexes of the donors have reported potential gender differences in the results of stem cell treatment of certain diseases [4345], and these may be related to the expression of hormonal receptors [46, 47]. hWJSCs derived from Wharton's Jelly of the umbilical cord have been reported to possess the properties of both mesenchymal and embryonic stem cells [48].…”
Section: Discussionmentioning
confidence: 99%
“…The differentiated cells were dissociated with Acutase (Innovative Cell Technologies, San Diego, CA) and prepared for magnetic-activated cell sorting (MACS) and uorescence-activated cell sorting (FACS) of CD31 + /CD34 + vascular progenitor cells (VPCs) [24]. Brie y, the cells were rst immunolabeled with CD34 microbeads for MACS (Miltenyi Biotec, Auburn, CA), and magnetic labeling was performed according to the manufacturer's instruction.…”
Section: Directed Differentiation Of Human Pluripotent Stem Cells To mentioning
confidence: 99%
“…Total RNA (1 µg) was reverse transcribed into cDNA using the M-MLV reverse transcriptase system (Thermo Scienti c). PCR primers were described previously [17,24], except human TIMP2 (Sense: AAGCGGTCAGTGAGAAGGAA; Anti-sense: GATGTTCAAAGGGCCTGAGA), rat MMP2 (Sense: GTAAAGTATGGGAACGCTGATGGC; Anti-sense: CTTCTCAAAGTTGTACGTGGTGGA) and rat TIMP2 (Sense: ACACGCTTAGCATCACCCAGAA; Anti-sense: CAGTCCATCCAGAGGCACTCAT The slides were visually scored by four people separately for elastin length (1 = short, 2 = moderate, 3 = long), thickness (1 = thin, 2 = moderate, 3 = thick) and density (1 = sparce, 2 = moderate density, 3 = dense), collagen density (1 = sparce, 2 = moderate density, 3 = dense). The scorers were blinded to the group assignments.…”
Section: Rna Extraction and Quantitative Reverse Transcriptionpolymermentioning
confidence: 99%